2011
DOI: 10.1002/eji.201041295
|View full text |Cite
|
Sign up to set email alerts
|

DUSP4 deficiency enhances CD25 expression and CD4+ T‐cell proliferation without impeding T‐cell development

Abstract: Summary The differentiation and activation of T cells are critically modulated by MAP kinases, which are in turn feed-back regulated by dual-specificity phosphatases (DUSPs) to determine the duration and magnitude of MAP kinase activation. DUSP4 (also known as MKP2) is a MAP kinase-induced DUSP member that is dynamically expressed during thymocyte differentiation. We generated DUSP4-deficient mice to study the function of DUSP4 in T-cell development and activation. Our results showed that thymocyte differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 41 publications
5
63
1
Order By: Relevance
“…DUSP10 (also named MKP5) is a positive regulator in T cell proliferation and T cell-mediated immune responses (22). DUSP4 (also named MKP2) suppresses CD4 + T cell proliferation but induces normal Th1/Th2 responses following KLH immunization (23), whereas DUSP4 enhances Th1 responses following Leishmania mexicana infection (21). To our knowledge, our study demonstrates for the first time a novel immune function for DUSP14 in T cells in vivo.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…DUSP10 (also named MKP5) is a positive regulator in T cell proliferation and T cell-mediated immune responses (22). DUSP4 (also named MKP2) suppresses CD4 + T cell proliferation but induces normal Th1/Th2 responses following KLH immunization (23), whereas DUSP4 enhances Th1 responses following Leishmania mexicana infection (21). To our knowledge, our study demonstrates for the first time a novel immune function for DUSP14 in T cells in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…Only two DUSPs (DUSP4 and DUSP10) are reported to be involved in T cell activation and T cell-mediated immune responses using KO mice (21)(22)(23). DUSP10 (also named MKP5) is a positive regulator in T cell proliferation and T cell-mediated immune responses (22).…”
Section: Discussionmentioning
confidence: 99%
“…29 Similar to DUSP6, 53 DUSP4 dephosphorylates ERK and c-Jun N-terminal kinases, 54,55 but also signal transducer and activator of transcription 5, and thereby regulates IL-2 signaling. 56 In vitro, we have shown that DUSP4, but not DUSP6, transcription is upregulated after successive TCR engagement in healthy CD4…”
Section: Discussionmentioning
confidence: 90%
“…In Figure 4C, we show a heat map based on hierarchical clustering of 30 selected immune activation genes in which H3K27me3 enrichment changed in either direction after activation as a function of time (resting, 1, 5 and 14 days). One gene that dramatically loses the H3K27me3 mark during activation and differentiation is DUSP4, which plays a key role in T cell proliferation (43). This gene is heavily enriched for H3K27me3 at rest in naïve and memory cells, progressing to low H3K27me3 enrichment after activation (Figure 4C–D) for both cell types with concurrent and dramatic upregulation of RNA expression by 1 day in naïve cells (Figure 4E).…”
Section: Resultsmentioning
confidence: 99%